Author Correction: Gene correction for SCID-X1 in long-term hematopoietic stem cells - Mara Pavel-Dinu (Nature Portfolio, 2019)
The original version of this Article omitted the following from the Acknowledgements: “G.B. acknowledges the support from the Cancer Prevention and Research Institute of Texas (RR140081 and RR170721).”This has now been corrected in both the PDF and HTML versions of the Article.